Perbedaan Penggunaan Tabung K2EDTA dan K3EDTA Terhadap Hasil Pemeriksaan Kadar Hemoglobin dan Jumlah Eritrosit pada Pasien Sebelum dan Sesudah Hemodialisis - Ananda Putri Purwanti; Suci Indah Astuti; Siti Raudah; Khoirul Anam (KOLONI, 2026)
Chronic kidney disease (CKD) patients undergoing hemodialysis are prone to anemia due to decreased erythropoietin production, making hemoglobin (Hb) level and erythrocyte count examinations important for monitoring patient condition. The accuracy of hematology results is influenced by pre-analytical factors, including the type of anticoagulant tube used, namely K2EDTA (dry spray) and K3EDTA (liquid). This study aimed to determine the difference in Hb level and erythrocyte count between K2EDTA and K3EDTA tubes in patients before and after hemodialysis at RSUD Kudungga, East Kutai. This quasi-experimental study used a pre-post test design involving 34 respondents selected through total sampling. Venous blood samples were collected before and after hemodialysis, placed into K2EDTA and K3EDTA tubes, and examined using a hematology analyzer. Data were analyzed using the Wilcoxon Signed Rank Test and Paired Samples t-Test. The results showed that mean Hb and erythrocyte count significantly increased after hemodialysis in both tube types (p < 0.001), presumably due to hemoconcentration from ultrafiltration. Comparison between tubes showed a significant difference before hemodialysis (p < 0.001) but no significant difference after hemodialysis (Hb p = 0.175; erythrocytes p = 0.463). It is concluded that K2EDTA and K3EDTA tubes produce relatively comparable results and both can be used for hematology examination in hemodialysis patients according to standard laboratory procedures.